Depression is a stronger predictor of the risk to consider work disability in early arthritis than disease activity or response to therapy. Issue 1 (20th February 2015) - Callhoff, Johanna; Albrecht, Katinka; Schett, Georg; Zink, Angela; Westhoff, Gisela
Abstract : Objectives: To evaluate the factors that influence patients with early inflammatory arthritis to consider a disability pension. Methods: A total of 528 patients aged 63 or younger from an early arthritis cohort with a mean symptom duration of 3 months at inclusion were asked at 12 and 24 months whether they were considering applying for, had applied for or were receiving a disability pension because of arthritis. Possible predictors were analysed with univariate and multivariate logistic regression. Results: 69 patients (13%) were considering, had applied for or were receiving a disability pension. Univariate predictors were older age, disease activity, several patient-reported outcomes and depression. In a multivariate analysis, age, days on sick leave, impairment of physical function and depression were predictive for considering a disability pension (OR for severe vs no depression: 3.85, 95% CI 1.43 to 10.4). Conclusions: In patients with early arthritis, depression appears to be a stronger predictor of the risk to consider applying for work disability pension than the features of disease activity. Patients at risk could be identified with one single depression statement. This finding should prompt physicians to react early to signs and symptoms of depression to help patients to maintain their ability to work.